Auricular point acupressure in patients with chronic low back pain: A literature study - Ervin Septian Dewi; Masfuri Masfuri; Liya Arista (Alma Ata University Press, 2023)
Background: Chronic low back pain is defined as pain that persists for 12 weeks or more and is a major health problem worldwide and is associated with high medical costs, decreased productivity, and disability. The use of analgesics with nonsteroidal anti-inflammatory drugs or opioids is one of the most common strategies to manage CLBP, but is not free from various adverse side effects. The use of other effective interventions to control pain including non-opioid medications, topical treatments, physical modalities, and complementary and alternative therapies is needed to reduce the side effects resulting from the use of pharmacological therapies. Auricular Point Acupressure is one of the complementary strategies of Traditional Chinese Medicine (TCM) that is widely used clinically to treat pain. APA may be useful for acute or chronic pain, either alone or in combination with other treatments.Objectives: To analyze the effectiveness of Auricular Point Acupressure for chronic low back pain.Methods: Literature review through online databases namely: Google Scholar, PubMed, EBSCOhost, and Scopus on articles with free full-text criteria, using Indonesian or English, publication in the last 10 years (2013-2022), and research designs of clinical trials, randomized controlled trials, systematic reviews, meta- analysis. The article search used the keywords (low back pain OR low back pain OR back pain) AND (auriculotherapy OR auricular therapy OR auricular acupressure OR ear acupressure) AND (pain OR disability).Results: 50 articles were found with 5 articles meeting the inclusion criteria. Of the five articles, the majority explained that the use of Auricular Acupressure is relatively safe and effective for reducing chronic low back pain, some articles showed a decrease in disability rates and improved sleep quality.Conclusions: Auricular Point Acupressure can be considered a relatively safe and effective complementary therapy fopr reducing chronic low back pain.